Pengaruh Relationship Marketing, Fasilitas, Kualitas Pelayanan Terhadap Kepuasan Pelanggan Komunitas Coffee And Space Surabaya Pada Kalangan Mahasiswa Di Surabaya - Nanda, Septi Calista; Mulyati, Diana Juni; Nasution, Ute Chairuz M (STAI Denpasar Bali, 2025)
Increasingly fierce business competition requires businesses to be able to meet the needs and desires of customers in order to create long-term satisfaction and loyalty. Komunitas Coffee and Space is one of the coffee shop businesses in Surabaya that targets students by offering a comfortable atmosphere for studying, discussing, and relaxing. This study aims to determine and analyze the effect of Relationship Marketing, Facilities, and Service Quality on Customer Satisfaction among students in Surabaya. The research method used is a quantitative approach with survey techniques. Data was collected from 96 respondents through non-probability incidental sampling technique. Data analysis includes validity, reliability, classical assumption test, multiple linear regression, t test, F test, and coefficient of determination (R²). The results showed that partially, Relationship Marketing, Facilities, and Service Quality have a significant effect on Customer Satisfaction. In addition, the three variables simultaneously also have a significant effect on Customer Satisfaction at Komunitas Coffee and Space. These findings indicate that improving the quality of relationships with customers, adequate facilities, and good service quality are very important in creating customer satisfaction. Therefore, the management of Komunitas Coffee and Space is advised to continue to strengthen these three aspects in order to increase customer satisfaction. Keywords: Relationship Marketing, Facilities, Service Quality, Customer Satisfaction, Students